Survey of the research capacity of clinical psychologists in Ireland. Issue 3 (11th July 2016) - McHugh, Patrick; Corcoran, Mark; Byrne, Michael
Abstract : Purpose: – The purpose of this paper is to profile the research activity, research skills and enablers of research of clinical psychologists in the Republic of Ireland. Design/methodology/approach: – All clinical psychologists working in the Health Service Executive (HSE) or HSE-funded organisations were requested to complete an online survey examining their research capacity. A total of 170 clinical psychologists completed the survey, with an estimated response rate of 20-25 per cent. Findings: – Within the preceding two years, 60 per cent ( n =102) of the clinical psychologists sampled had engaged in research. These research active participants were involved with a median of three projects and the majority spent 10 per cent or less of their work time engaged in research. The weakest research skills of research active and research inactive participants were applying for research funding and publishing research. Research active participants indicated a reliance on their own personal motivation to maintain their research activity and indicated a need for more protected time for research. Practical implications: – Managers within the health service need to be incentivised to allocate protected work time for research that directly contributes to service provision. Greater collaboration with academic institutions is needed with regard to targeting the research skills development of clinical psychologists, as well as identifying opportunities for collaborative research. Originality/value: – This is the first survey to profile the research activity and skills of clinical psychologists in the Republic of Ireland and provides an evidence base for future research capacity development.